New solitary wave solutions for the conformable Klein-Gordon equation with quantic nonlinearity - Inc, Mustafa; Rezazadeh, Hadi; Vahidi, Javad; Eslami, Mostafa; Akinlar, Mehmet Ali; Ali, Muhammad Nasir; Chu, Yu-Ming (AMER INST MATHEMATICAL SCIENCES-AIMS, 2020)
We present new exact solutions in the form of solitary waves for the conformable Klein-Gordon equation with quintic nonlinearity. We use functional variable method which converts a conformable PDE to a second-order ordinary differential equation through a traveling wave transformation. We obtain periodic wave and solitary wave solutions including particularly kinkprofile and bell-profile type solutions. The present method is a direct and concise technique which has the potential to be applicable to many other conformable PDEs arising in physics and engineering.
Keywords: functional variable technique; conformable derivative; conformable Klein-Gordon with quantic nonlinearity; exact wave solutions; FUNCTIONAL VARIABLE METHOD; EVOLUTION; DYNAMICS; SOLITONS; Mathematics